The transits of extrasolar planets with moons - Kipping, David M. (Springer theses., 2011)
Can we detect the moons of extrasolar planets? For two decades, astronomers have made enormous progress in the detection and characterisation of exoplanetary systems but the identification of an exomoon is notably absent. In this thesis, David Kipping shows how transiting planets may be used to infer the presence of exomoons through deviations in the time and duration of the planetary eclipses. A detailed account of the transit model, potential distortions, and timing techniques is covered before the analytic forms for the timing variations are derived. It is shown that habitable-zone exomoons above 0.2 Earth-masses are detectable with the Kepler space telescope using these new timing techniques.